Immediate Effects of Blood Flow Restriction Combined with Neuromuscular Electrical Stimulation in Female Amateur Football Players: A Pilot Trial - Irene Afán-Argüín; Carlos Fernández-Morales; Luis Espejo-Antúnez; Manuel Albornoz-Cabello; Felipe León-Morillas; María de los Ángeles Cardero-Durán (Applied Sciences, 2023)
We aimed to investigate the acute effects of blood flow restriction (BFR) combined with neuromuscular electrical stimulation (NMES) on muscle strength, thigh circumference, and knee joint reposition sense in female amateur football players, as well as to determine whether this procedure is safe. Methods: This was a pilot trial. Twenty female amateur football players were randomized into two groups: group 1 (n = 10) received a single NMES session; group 2 (n = 10) received NMES + BFR. The measured variables included maximal voluntary eccentric contraction (MVEC) and maximal voluntary concentric contraction (MVCC), thigh circumference, and knee joint reposition sense test. The type of electrical current used was TENS (symmetrical biphasic rectangular pulse, 350 μs, and 50 Hz), combined simultaneously with active knee extension (75 repetitions in 4 sets, 20% MVCC, 30 s rest between sets), for both groups. Group 2 had BFR added (80% of arterial occlusion pressure). Results: Statistically significant differences (p ≤ 0.05) were obtained for thigh circumference in both groups. The comparison between groups did not show statistically significant differences (p ≤ 0.05) in MVEC, MVCC, thigh circumference, or the knee joint reposition sense test. Conclusions: Both the isolated NMES intervention and its combination with BFR induced immediate changes in thigh circumference without impairing the muscle strength or proprioceptive ability of the football players. However, these results should be interpreted with caution, and future studies including a control group and isolated BFR application are needed.